Answer:
b=c-ax/y
Step-by-step explanation:
1) ax + by = c
-ax
2) by = c - ax
3) by/y = b and c - ax/y
4) b = c-ax/y
Answer: 3 or -3
Step-by-step explanation:
4 - |x| = 1
First subtract 4
-|x| = -3
The | | sign makes it both positive and negative
So -|3| and -|-3| will = -3
1.
f(x) = x
g(x) = x + 3
For each x value you use in f(x) and g(x), the corresponding y value in g(x) is always 3 more than in f(x). If each y-coordinate is 3 more, that means the graph is shifted 3 units up. The graph of f(x) is shifted 3 units up to create the graph of g(x).
2.
The first term is -0.5.
Then each term goes up by 0.25.
1st term: -0.5
2nd term: -0.5 + 0.25 = -0.5 + 0.25(1)
3rd term: -0.5 + 0.25 + 0.25 = -0.5 + 0.25(2)
4th term: -0.5 + 0.25 + 0.25 + 0.25 = -0.5 + 0.25(3)
nth term: -0.5 + 0.25(n - 1)
-0.5 + 0.25(n - 1) = -0.5 + 0.25n - 0.25 = -0.75 + 0.25n = 0.25n - 0.75
Answer is C.
Answer:
34.78 is the answer to ur question